Hubungan Kesegaran Jasmani dengan Teknik Dasar Bermain Kasti Siswa SMP Negeri 13 Kota Lubuklinggau - Tri Septia Sari; Muhammad Suhdy; Muhammad Supriyadi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to determine the relationship between the level of physical fitness and playing baseball for class VIII students at SMP Negeri 13 Lubuklinggau City. This study used survey methods and data collection techniques in the form of tests and measurements. The subjects in this study were class VIII students aged 13-15 years at SMP Negeri 13 Kota Lubuklinggau, with a total of 12 students, consisting of 5 male students and seven female students. The data collection technique used a test and measured the level of physical fitness measured by the TKJI published by the Ministry of National Education in 2010, which consisted of a 50-meter run, hanging your elbows, lying down for 60 seconds, jumping straight up, and running 1000 meters. And Saptono's modified baseball game test in 2013 consisted of the accuracy of throwing a baseball, hitting a baseball, catching a baseball, and running 50 meters. The data analysis technique uses product-moment correlation analysis. The results of the research are based on calculations. The results of the data normality test show that the data is declared normal, and the data linearity test is declared linear so that the research data can be carried out with statistical tests with SPSS 21. The relationship between the level of physical fitness and playing baseball is 1. ,52. Based on the results of testing the hypothesis P <0.05, the hypothesis states the regression line is significantly linear. In conclusion, there is a significant correlation between physical fitness and playing baseball for students at SMP Negeri 13 Lubuklinggau City. Keywords: Middle School Students, Playing Kasti, Relationship, TKJI,